The Effect of Online Brand Experience on Online Brand Loyalty Through Brand Attachment as a Mediation and Service Quality as Moderation - Atmaja, Dodi Ria; Sari, Dian Indah (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: Online brand loyalty has gained increasing attention alongside the rapid development of digital technology and the growing complexity of consumer behavior in e-commerce. Intense competition among digital platforms requires businesses to understand how online brand experience (OBE) and brand attachment (BA) contribute to customer loyalty. Method: This study examined the effect of online brand experience on online brand loyalty (OBL), with brand attachment as a mediating variable and service quality as a moderating variable. A quantitative approach was employed involving 100 Shopee users in Greater Jakarta, aged 17-50 years, who had completed at least two purchases through the Shopee application during the preceding three months. Respondents were selected using purposive sampling, and data were collected through an online questionnaire. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: Online brand experience had significant positive effects on online brand loyalty and brand attachment. Brand attachment also had a significant positive effect on online brand loyalty and significantly mediated the relationship between online brand experience and online brand loyalty. However, service quality did not significantly moderate the relationship between online brand experience and online brand loyalty. Therefore, four of the five proposed hypotheses were supported. Conclusion: Positive online brand experiences strengthen customers’ emotional attachment to a platform, which subsequently promotes long-term loyalty. These findings highlight the importance of creating memorable and engaging digital experiences rather than relying solely on service quality. The study provides practical implications for e-commerce platforms seeking to strengthen customer loyalty through improved user experiences and stronger emotional relationships with their brands.